2015
DOI: 10.4292/wjgpt.v6.i4.156
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and inflammatory bowel diseases: Current perspectives, risks and patient management

Abstract: Manas K made critical revisions of the manuscript; Becker F and Alexander JS contributed equally as senior authors. Conflict-of-interest statement:There are no known conflicts of interest. The authors (Pegah Hosseini-Carroll, Monica Mutyala, Abhishek Seth, Shaheen Nageeb, Demiana Soliman, Moheb Boktor, Ankur Sheth, Jonathon Chapman, James Morris, Paul Jordan, Kenneth Manas, Felix Becker, and J Steven Alexander) have no relevant financial considerations related to this proposal, and the study was not supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…It is recommended that IBD remission should be achieved prior to conception. [18][19][20] Quiescent disease is believed to have minimal impact on the course and outcome of pregnancy, whereas patients with active disease at conception have increased rates of spontaneous abortion, pre-term birth, low birth weight and infants that are small for gestational age. 18,[21][22][23] Interpretation of the impact of IBD disease activity on pregnancy outcome in vedolizumab-treated females is confounded by incomplete availability of data and the small numbers of patients; however, generally more severe disease activity was recorded in individuals experiencing a pre-term live birth or spontaneous abortion than in those with a fullterm pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended that IBD remission should be achieved prior to conception. [18][19][20] Quiescent disease is believed to have minimal impact on the course and outcome of pregnancy, whereas patients with active disease at conception have increased rates of spontaneous abortion, pre-term birth, low birth weight and infants that are small for gestational age. 18,[21][22][23] Interpretation of the impact of IBD disease activity on pregnancy outcome in vedolizumab-treated females is confounded by incomplete availability of data and the small numbers of patients; however, generally more severe disease activity was recorded in individuals experiencing a pre-term live birth or spontaneous abortion than in those with a fullterm pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To control disease optimally and maintain remission, many patients require therapy throughout pregnancy. 19,20,22,24 Consequently, it is vital to consider the effect of IBD medications on foetal health. Generally, the greatest risk to mother and foetus during pregnancy is active IBD, not the medication used to treat it.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease activity at the time of conception could determine the clinical course the patients with CD will experience during pregnancy . Increased disease activity has been shown to effect female fertility and pregnancy outcomes .…”
Section: Case Descriptionmentioning
confidence: 99%
“…IBD flare-ups are often due to medication discontinuation during pregnancy, lactation and smoking resumption following birth[10]. Approximately one-third of patients have active disease during conception[11]. Nielsen et al[12] reported that the yearly exacerbation rate is 34% during pregnancy and 32% in non-pregnancy.…”
Section: Introductionmentioning
confidence: 99%